Confining effect of carbon-nanotube configuration on phase behavior of hard-sphere fluid - Huang, Huan Cong (2013)
We capture the effects of the structured surface on a phase transition of hard-sphere fluids. The confining environment follows single-walled carbon nanotube (SWCNT) configuration. For careful discrimination of the surface-chirality effect, hard-core potentials are applied to carbon atoms, and further their positions are fixed. In this way, equation of states and microstructures of the confined particles are intrinsically obtained based on the SWCNT chirality as well as the diameter. We observed three branches indicating fluid-like and solid-like phases with onsets of freezing and melting. We found that freezing and melting of fluid particles are very sensitive to the surface chirality in small-diameter SWCNT, which especially holds a single layer of fluid particles. In those SWCNTs, spreading pressures are found to be lower than those of smooth-surface cylindrical pores. The surface chirality has less impact on the phase change of confined fluids for large-diameter SWCNT, of which diameter is a dominant factor.